PJMHS 2021
DOI: 10.53350/pjmhs211551482
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Covid-19 Lockdown on Body Mass Index, Depression, Anxiety and Stress among Medical Students

Abstract: The Covid-19 pandemic has wreaked havoc throughout the world, with 150 million cases to date and over 3 million lives claimed worldwide. Objectives: To explore the impact of the Covid-19 lockdown on psychological health parameters i.e. depression, anxiety and stress as well as on body mass index among medical students studying in a private medical college in Pakistan. Study Design: Experimental study. Methodology: This study with enrolled students (n=233) was carried out after ethical review committee’s (ERC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 12 publications
0
9
2
Order By: Relevance
“…The quality assessment of the studies using the NOS ranged from 3 to 6, and the median was 4 (Table S3). Of the 74 included studies, there were 67 with data that could be meta-analyzed for at least one of the four outcomes [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][79][80][81][82][83][84][86][87][88][89][90][91][92][93][94][95]…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The quality assessment of the studies using the NOS ranged from 3 to 6, and the median was 4 (Table S3). Of the 74 included studies, there were 67 with data that could be meta-analyzed for at least one of the four outcomes [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][79][80][81][82][83][84][86][87][88][89][90][91][92][93][94][95]…”
Section: Search Resultsmentioning
confidence: 99%
“…As described in Figure 1, a total of 20,955 articles were identified from the search, and after the removal of 7322 duplicates, 13,633 articles were screened for title and abstract. A full‐text screening was conducted on 296 articles, and 74 met the final inclusion and exclusion criteria and were included in the review 39–112 . Table 1 summarizes the study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were also administered in other parts of Asia, including Pakistan, Japan, Bangladesh, Kazakhstan, Nepal, and Singapore. At Harian Medical College in Pakistan, a study of 233 students showed a significant decrease in the level of depression and an increase in the level of anxiety and stress among medical students (Masud et al, 2021). At the Okayama University School of Medicine in Japan, a survey of 473 medical students found that students' mental health status significantly worsened after the Japanese State of Emergency regarding the pandemic was implemented (Nishimura et al, 2021).…”
Section: Rest Of Asia Excluding the Middle Eastmentioning
confidence: 99%